Thru-Reflect-Line (Trl) Calibration On Multilayer Substrate Integrated Waveguide (Siw) For X-Band Frequency Range - Cha, Hong Ye (2017)
Scattering-parameters (S-parameters) are important to be evaluated in order to ascertain the hardware prototype can be designed according to the specifications. Various calibration methods have been applied to the network analyser to obtain the S-parameters, such as shortopen- load-thru (SOLT) and thru-reflect-line (TRL). Substrate integrated waveguide (SIW) demonstrates low loss, compact size, and ease for integration with the planar circuits. In this research, MTRL calibration is proposed to predict the single- and multilayer- SIW. The analytical modelling of MTRL calibration, and the FE models of the prototypes are discussed and simulated. The S-parameters, such as insertion loss, bandwidth, and resonant frequency, can be measured in the frequency range of 8.0 GHz – 13.0 GHz. The S-parameters of the prototype are measured by the proposed MTRL kits and compared with commercial SOLT kits, and validated by FE results. The comparison results between MTRL, SOLT and FE models for single layer SIW are discussed and analysed. MTRL calibration on single layer SIW shows deviation of 0 % - 5.0 % of centre frequency, larger operating bandwidth and closer insertion loss with respect to FE models. Moreover, a good agreement is achieved between the FE model and experimental results using MTRL calibration for double layer SIW with rectangular slot. A finite model of double layer SIW with rectangular slot shows four different resonant frequencies with 2.71 dB insertion loss. The measurement obtained using the SOLT method displays three different resonant frequencies with 3.41 dB insertion loss. In contrast, the measurement obtained using MTRL calibration displays four different resonant frequencies and 2.87 dB insertion loss. Based on these findings, MTRL calibration predicts more accurately pertaining to single- and multi- layer SIW with close resonant frequencies and low insertion loss as compared with that of the SOLT method.